Discontinuation rate of dual antiretroviral therapy with dolutegravir plus lamivudine in people living with HIV: a systematic review (Research, Society and Development, 2022)
Antiretroviral therapies are used as a way to improve the life expectancy of people living with HIV. With the reduction of adverse effects, dual therapy with dolutegravir (DTG) plus lamivudine (3TC) has proved to be a viable option. However, even with similar efficacy to triple therapy, there is still a lack of focus on treatment discontinuation rates. For this reason, the objective of this work was to evaluate the discontinuation rate of dual antiretroviral therapy with DTG plus 3TC in people living with HIV. A systematic review was performed in PubMed, SciElo and Scopus databases, from the selection of cohort studies that reported the discontinuation rate with the use of dual therapy with DTG plus 3TC. Fourteen articles, eight are retrospective studies and six are prospective studies were selected. The population consisted of 2,666 individuals, with a mean age of 50.4 years, 75.2% of which were male. The discontinuation rate of dual therapy with DTG plus 3TC described in the studies ranged from 0.0% to 22.4%. A total of 364 subjects discontinued dual therapy with DTG plus 3TC, with the observed discontinuation rate being 13.7% (95%CI 13.0-14.4%). The main reasons for discontinuation were neuropsychiatric events (19.5%), virologic failure (10.7%) and gastrointestinal toxicity (8.8%). Even with the benefits provided by dual therapy, some factors still contribute to treatment discontinuation, and it is still possible to observe a high rate of treatment discontinuation using the dual therapy of DTG plus 3TC.